Mass determination of the charged pion, using high precision X-ray spectroscopy - Anagnostopoulos, et al., D. F. (HNPS Advances in Nuclear Physics, 2020)
X-ray transitions in pionic nitrogen were measured using a curved crystal spectrometer. From the transition energy, calibrated with the help of the copper Ka1,2 electronic transition, a value for the charged pion mass of (139.57071± 0.00053) MeV/c2 was deduced. In order to reduce the uncertainty of the charged pion mass in the level of 1 ppm, we propose the determination of pionic transition energy based on the more precisely known energies and line shapes of muonic transitions.